Elementary Physical Educator Assessment in Qualitative Teaching Elements - Vasiliadou, Όλγα; Hristakis, Εµµανουήλ; Derri, Βασιλική; Emmanouilidou, Κυριακή (Inquiries in Physical Education and Sport, 2006)
The purpose of the present study was to assess the quality of instruction of physical education teachers in elementary school. The subjects were twelve physical educators (6 men and 6 women), aged 33-40 yrs (M=36.58, SD=2.81), with at least five years experience in elementary school teaching, who were asked to teach two basic manipulative skills (the overhand throwing and catching) for eight consecutive lessons. The students were 207 seven year olds, (M=6.95, SD=.36) first grade children (103 boys, 104 girls). A total of 96 lessons were videotaped, tape-recorded, and then evaluated according to the Qualitative Measures of Teaching Performance Scale (QMTPS, Rink & Werner, 1989). The results were evaluated in a climate of one hundred degrees and indicated that teachers were near a hundred in clarity (98.9%) and appropriate student responses (97.7%). Their total QMTPS score fluctuated in moderate levels (43.7%) in congruent feedback (40.2%) and demonstration (34.2%). In the three categories related to adequacy, accuracy and quality of critical cues, their performance was very low (14.6%, 6.7% and 13.7% respectively). From the results it can be conducted that the physical educators are very capable in presenting the activities. On the contrary, improvement is needed in providing full demonstration, sort inclusive critical cues, and providing congruent feedback.